Dolutegravir/Abacavir/Lamivudine versus Current ART in Virally Suppressed Patients (STRIIVING): A 48-Week, Randomized, Non-Inferiority, Open-Label, Phase IIIb Study. Issue 4 (May 2017) - Trottier, Benoît; Lake, Jordan E; Logue, Ken; Brinson, Cynthia; Santiago, Lizette; Brennan, Clare; Koteff, Justin A; Wynne, Brian; Hopking, Judy; Granier, Catherine; Aboud, Michael
Background: Simplified dosing regimens are important for patients who face challenges in adhering to HIV-1 therapy. We investigated the safety and virological efficacy of switching to once-daily abacavir/dolutegravir/lamivudine (ABC/DTG/3TC). Methods: The STRIIVING study was a randomized, open-label, Phase IIIb study in adults with HIV-1 RNA <50 copies/ml on antiretroviral therapy (ART) at enrolment (ClinicalTrials.gov identifer, NCT02105987). Subjects were randomly assigned to switch to ABC/ DTG/3TC once daily for 48 weeks (early-switch group) or continue current ART for 24 weeks and then switch to ABC/DTG/3TC (late-switch group). The primary end point was the proportion of subjects with HIV-1 RNA <50 copies/ml at week 24. Results: Of 553 subjects enrolled, 275 were randomly assigned to switch immediately to ABC/DTG/3TC and 278 continued on current ART. At week 24, 85% and 88% of subjects who switched to ABC/DTG/3TC or remained on current ART, respectively, were virologically suppressed, indicating that ABC/DTG/3TC was non-inferior (difference in proportion, -3.4%; 95% CI -9.1, 2.4). At week 48, 83% and 92% were virologically suppressed in the earlyand late-switch groups, respectively. Adverse events were reported more frequently with ABC/DTG/3TC (66%) than with current ART (47%) by week 24, and in the late-switch group, 60% of subjects reported adverse events post-switch. Pharmacokinetic data supported immediate switch. HIV Treatment Satisfaction Questionnaire scores improved in participants switching to ABC/DTG/3TC versus current ART. Conclusions: Data demonstrating non-inferiority of switching to ABC/DTG/3TC versus continuing current ART support ABC/DTG/3TC as an option when considering switch regimens in HIV-1-infected adults with stable viral suppression.